Counselling for Teachers' Motivation on Academic Performance of Secondary School Students in Abeokuta South Local Government Area, Ogun State, Nigeria - Oba-Adenuga, Olusegun Adeleke (NIU Journal of Humanities, 2022)
This study examined the counselling for teachers' motivation on academic performance of secondary school students in Abeokuta South Local Government Area of Ogun State, Nigeria. The study adopted a descriptive survey research design; three hypotheses were postulated to guide the study. The study used samples of 15 teachers and 180 students; data collected for the study was through questionnaire tagged "Teachers Motivation and Students' Academic Performance Inventory (TMSAPI)". And was used to test the hypotheses using Pearson Correlation Coefficient and tested at 0.05 level of significance. The result of this study reveals a significant relationship between teachers' motivation and students' academic performance. Also, the result shows a significant relationship between strategies used to motivate teachers and students' academic performance. Finally, the result reveals a significant relationship between condition of service of teachers and academic performance. The result recommended that Government should ensure regular payment of teachers' salaries and prompt promotion as at when due. Keywords: Teachers' Motivation, Academic Performance, Counselling, Condition of service